2011
DOI: 10.1310/hpj4604-254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Medication Discrepancies Occurring at the Time of Discharge from an Adult State Psychiatric Inpatient Facility

Abstract: Purpose To retrospectively measure the frequency of medication discrepancies occurring at hospital discharge and to characterize these discrepancies. Methods All consecutive discharges from an adult state psychiatric hospital with a length of stay ≥2 days were retrospectively evaluated for medication discrepancies occurring at the time of discharge. The content of the handwritten discharge plan was compared to the medication administration record from the last day of admission to identify medication discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Findings from this observational study differs from similar studies in the USA, both in the magnitude of discontinuation: reported to be between 12% and 19% for thyroid and antithrombotic medications; and in terms of the impact of hospitalisation, with hospitalisation being independently associated with discontinuation, when assessed using pharmacy dispensing data 8–10 41. The impact of hospitalisation appears to be context and health system-specific, with some studies not finding a relationship between discontinuity and hospitalisation 42–44. We found that increased number of medications was not associated with discontinuation; in the respiratory inhalers group patients were less likely to be discontinued if they had increased numbers of medications 34 37–39 45–47.…”
Section: Discussioncontrasting
confidence: 91%
“…Findings from this observational study differs from similar studies in the USA, both in the magnitude of discontinuation: reported to be between 12% and 19% for thyroid and antithrombotic medications; and in terms of the impact of hospitalisation, with hospitalisation being independently associated with discontinuation, when assessed using pharmacy dispensing data 8–10 41. The impact of hospitalisation appears to be context and health system-specific, with some studies not finding a relationship between discontinuity and hospitalisation 42–44. We found that increased number of medications was not associated with discontinuation; in the respiratory inhalers group patients were less likely to be discontinued if they had increased numbers of medications 34 37–39 45–47.…”
Section: Discussioncontrasting
confidence: 91%
“…When viewed at the whole discharge level, our study supports findings from earlier research conducted in the United States 15,21 which found that PEs affected approximately 1 in 5 discharge prescriptions and were thus a common safety threat at the interface between care settings. This has been exemplified following a recent review of patient safety incidents arising at mental health hospital discharge that were reported in England and Wales, finding that medication problems such as omissions and dosing errors were involved in 22% of incidents causing moderate, low and no harm.…”
Section: Implications Of Findingssupporting
confidence: 87%
“…One UK study investigating the quality of medicines information transfer between primary care and a mental health NHS trust published in 2002 found that 16% of medicines were affected by unintentional discrepancies when discharge summaries were compared to medication issued by the GP after discharge supplies had run out . Although more recent evidence from the United States, UK and Denmark reveals that unintentional medication discrepancies and errors continue to affect discharge prescriptions, other considerations have not been sufficiently explored, such as the quality of recording patients’ clerical (e.g. demographics, allergy status) information on discharges which is known to be a problem in UK general hospitals, as well as which factors may affect the risk of prescribing or clerical errors occurring and whether details of medicines changed during hospitalization were communicated or not.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…18 20 22 Omission of drugs on patient transfer may arise due to the inadequate communication of drug information, 8 35 an issue which may affect mental health settings more acutely given the increasing number of community services creating more care transfer interfaces. 13 36 37 One UK study found that 69% and 43%, respectively, of hospital admission and postdischarge medicines were affected by a medication discrepancy, 17 and more recently studies found that 56.2% of hospital admissions (UK based) 38 and 23.3% of discharges (USA based) 39 were affected, with the most common types being drug omissions. These studies highlight the importance of medicines reconciliation, a practice which is established in UK mental health hospitals 40 and which has shown value across hospital settings.…”
Section: Discussionmentioning
confidence: 99%